American Exceptionalism in Market Income Inequality: An Analysis Based on Microdata from the Luxembourg Income Study (LIS) Database - Janet C. Gornick; Branko Milanovic; Nathaniel Johnson (Luxembourg Income Study (LIS), 2017)
The US has exceptionally high inequality of disposable household income (i.e., income after accounting for taxes and transfers). Among working-age households (those with no persons over age 60), that high level of inequality is caused by a high level of market income inequality (i.e., income before taxes and transfers), paired with a moderate level of redistribution. In this paper, we look more deeply at market income inequality, focusing on its main component - labor income - across a group of 24 OECD countries. We disaggregate the working-age population into household types, defined by the number and gender of the household's earners and the partnership and parenting status of its members. We concentrate on comparing US results with those of the other OECD countries. Our main finding is that high levels of labor income inequality in the US cut across diverse subgroups. We conclude that within-group inequality of labor incomes in the US is, in almost all groups, high by OECD standards. So it is neither an unusual household composition, nor unusually high mean labor incomes of some groups (nor indirectly, unusually low levels of redistribution), that explain high US disposable income inequality, but instead the fact that high and low labor incomes are universally spread across all household/demographic categories.
Keywords: D31; D33; 330; Wage distribution; earnings distributions; income inequality